Die griechische Übersetzung der Samuelbücher: Die Samuel-Septuaginta als Herausforderung für die alttestamentliche Textforschung - Wirth, Raimund (TC, 2017)
This paper is about the translation of the Septuagint of Samuel (1-2 Kingdoms) and its recensions. It starts with an overview of the current state of research, including aspects of the books' Hebrew textual history. An outline of the translation technique in the Greek books of Samuel follows. The author points out that the translator often worked quite literally, even though there are instances of free renderings as well. Regarding the use of tenses, the translation is characterized as intuitive and widely independent of the Hebrew Vorlage. Since the style in the books of Samuel is not very literary overall and falls short when compared with the translation of the Pentateuch, the author argues that the translation was made as a "private undertaking" and not for liturgical purposes. Finally, the author describes the special text-critical challenges in the so-called kaige section (2 Sam 10-24). As the Greek text in these chapters is solely transmitted in two recensional forms (kaige and Lucianic), careful reflection on the methodology of reconstructing the original translation (Old Greek) is needed. In this connection, the author pleads for a reassessment of the role of conjectures, which he considers necessary to match the character of the Old Greek in the area of verbal syntax.